2004
DOI: 10.1530/rep.1.00160
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma regulates endometrial cytokine expression, leukocyte recruitment and embryo development in the pig

Abstract: In pigs, uterine exposure to the constituents of semen is known to increase litter size but the underlying physiological mechanisms remain undefined. Studies in rodents and humans implicate immune modulating moieties in seminal plasma as likely candidates, acting through enhancing the receptivity of the female tract. In this study, the acute and longer term effects of seminal plasma on cytokine expression and leukocyte abundance in the pig endometrium during early pregnancy have been characterised. The reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 41 publications
11
184
1
4
Order By: Relevance
“…In addition to neutrophils a large number of antigen presenting cells (APCs) are recruited into the uterine endometrium, including macrophages and dendritic cells (DCs) expressing high levels of MHC class II [60,8]. This response has now been well characterised in other species including rabbit, horse, pig, and human [61][62][63][64]12].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
“…In addition to neutrophils a large number of antigen presenting cells (APCs) are recruited into the uterine endometrium, including macrophages and dendritic cells (DCs) expressing high levels of MHC class II [60,8]. This response has now been well characterised in other species including rabbit, horse, pig, and human [61][62][63][64]12].…”
Section: Post-insemination Inflammationmentioning
confidence: 99%
“…Moreover, some SP-proteins, once into the female genital tract after natural mating or AI, modulate the uterine immune response against the foreign semen, facilitating sperm transport [11], sperm-oocyte fusion [12] and the development of a healthy embryo [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that semen deposition in the human female reproductive mucosa results in the induction of a strong inflammatory response that includes the production of inflammatory cytokines and chemokines (7,9,10), the upregulation of cyclooxygenase-2 expression (11), the infiltration of the cervix by neutrophils, and the recruitment of dendritic cells (DCs) (9,12,13). This inflammatory response induced by semen has also been described in mice, pigs, rabbits, and other mammals, and appears to induce the adaptation of the female immune response to promote fertility (14,15).…”
mentioning
confidence: 99%